Amor est passio: The Authorship and Dating of De amore by Andreas Capellanus - Havas-Kovács, Dominika (Sapiens ubique civis, 2023)
Andreas Capellanus’ treatise on love, De amore has been interpreted in many different ways. Scholars agree on only one thing: this work presents a scholastic understanding of love in a rigorous and structured way. We are not sure of the identity of the author from the surviving documents, but he wrote in Latin in a French context sometime in the 12th century. In my study, I will explore who Andreas Capellanus might have been, as well as the supposed date of the work.